Voltage-gated calcium channels act upstream of adenylyl cyclase Ac78C to promote timely initiation of dendrite regeneration. - Hertzler, J.I.; Teng, J.; Bernard, A.R.; Stone, M.C.; Kline, H.L.; Mahata, G.; Kumar, N.; Rolls, M.M. (PLoS Genetics, 2024)
Most neurons are not replaced after injury and thus possess robust intrinsic mechanisms for repair after damage. Axon injury triggers a calcium wave, and calcium and cAMP can augment axon regeneration. In comparison to axon regeneration, dendrite regeneration is poorly understood. To test whether calcium and cAMP might also be involved in dendrite injury signaling, we tracked the responses of Drosophila dendritic arborization neurons to laser severing of axons and dendrites. We found that calcium and subsequently cAMP accumulate in the cell body after both dendrite and axon injury. Two voltage-gated calcium channels (VGCCs), L-Type and T-Type, are required for the calcium influx in response to dendrite injury and play a role in rapid initiation of dendrite regeneration. The AC8 family adenylyl cyclase, Ac78C, is required for cAMP production after dendrite injury and timely initiation of regeneration. Injury-induced cAMP production is sensitive to VGCC reduction, placing calcium upstream of cAMP generation. We propose that two VGCCs initiate global calcium influx in response to dendrite injury followed by production of cAMP by Ac78C. This signaling pathway promotes timely initiation of dendrite regrowth several hours after dendrite damage.